(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Cytostatic drugs used in the course of chemotherapy have a nephrotoxic effect, which leads to the development of renal failure and causes morphological changes in the organs of the digestive system, in particular in the small intestine. The aim of the study was to study the morphological and morphometric parameters of the small intestine in conditions of renal failure associated with chemotherapy, against the background of biocorrection with dandelion root. The study was conducted on an experimental model using histological and morphometric methods. The results showed that under the influence of chemotherapy, there is a decrease in the height of the villi, a decrease in the number of epithelial cells, and the development of inflammatory and degenerative changes. When applying biocorrection with dandelion root, there was a partial restoration of the mucosal structure and an approximation of morphometric parameters to normal values. The data obtained are of great scientific and practical importance for understanding changes in the small intestine during complications of chemotherapy and expand the possibilities of using natural biocorrective agents.